Guessing Games in The EFL Classroom: Promoting Speaking Skills in Indonesian Students - Nuryana, Amiatun (JADEs Journal of Academia in English Education, 2024)
One of the methods can be used by the teacher in teaching and learning process are through game. The aim of this research is to know the applying guessing game and non-guessing game technique on the students' speaking skill. The research design of this research is quantitative, and the kind is expremental design where the researcher try to give teatment to the students. There are two variables in this case which are called as expremental group and control. The researcher got the result of the research where Mx 1,4 and My 5,75 so that it can be concluded that the difference is 4.35. It is significance because when the students compare the result of the post test of control group and experimental group. The results of this research show that by using test, we know that a significance difference between the students taught by using guessing game and non using guessing game at the first level of SMP Al-Falah Assalam Sidoarjo. It means that the students taught by using guessing game have better skill than the students who are not taught by using guessing game. Keyword : game technique, guessing game, non-guessing game, speaking ability